THE EFFECT OF TRAINING AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT EDUCATIONAL INSTITUTIONS IN BANDUNG - Wardoyo, Trimanto Setyo; Budiningsih, Tatik; Kambono, Herman; Yasmin, Kirana Erlinda (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
The purpose of this study was to determine the effect of training and work discipline on employee performance at educational institutions in the city of Bandung. Job training and work discipline are the main factors that are thought to have a positive effect on work performance at companies in general. However, does the same thing happen to non-profit organizations such as educational institutions? Samples were taken from non-educator employees at educational institutions in Bandung, as many as 59 respondents through a questionnaire. The results of this study indicate that training and work discipline simultaneously have a significant effect on employee performance at educational institutions in Bandung. In addition, work discipline partially has a significant effect on work performance, but partially training does not have a significant effect on the work performance of non-educator employees at educational institutions in Bandung.